How different contexts of social capital are associated with self-rated health among Lithuanian high-school students - Dario Novak; Arunas Emeljanovas; Brigita Mieziene; Lovro Štefan; Ichiro Kawachi (Taylor & Francis Group, 2018)
Background. Adolescents' self-rated health is related to a number of sociodemographic and socio-economic factors, health-related behaviors, and their social environment. The impact of the latter is still not well explored. An adolescent's social environment is represented by the social capital, i.e. social resources that they can access. The relationships between various contexts of social capital (family, neighborhood, peers, and school) and self-rated health among adolescents are still unclear. Objective. This study aims to examine the relationships between various social capital contexts and self-rated health in Lithuanian adolescents. Methods. The current cross-sectional study includes a nationally representative sample of 1863 adolescents (51.4% were girls) aged 14-18 years. The indicators of self-rated health as well as indicators of social capital in family, neighborhood, and school contexts were assessed. The results of the relationships between self-rated health and contexts of social capital were calculated controlling for the following covariates: physical activity, psychological distress, gender, body mass index, and family socioeconomic status. Results. Results indicate that there are significant relationships between good self-rated health and a higher level of family support, neighborhood trust, and vertical school trust. In the final logistic regression model, while controlling for all covariates, a higher level of family support and neighborhood trust remain significant predictors of good self-rated health. Conclusions. Family support and neighborhood trust are important correlates of self-rated health in adolescents.